Prevalence of Human Cytomegalovirus in Breast Cancer: A Systematic Review - Nakhaie, Mohsen; Charostad, Javad; Ghaderi-Zefrehi, Hossein; Arabzadeh, Seyyed Ali Mohammad; Pourhosseini, Fatemeh; Makvandi, Manoochehr (Asian Pacific Journal of Cancer Biology, 2021)
Background: Breast cancer is the most common malignancy among women around the world, with several risk factors contributing to its progression. The role of infectious agents such as viruses in the progression of this cancer is relatively well-known, as a result of various studies in different geographical regions that reported the prevalence of cytomegalovirus in breast cancer. Objective: In this systematic review, we tried to examine the prevalence of cytomegalovirus in breast cancer. Materials and Methods: We conducted a comprehensive search of three databases: PubMed, Scopus, and Google Scolar up to January 21, 2021. Results: Out of 584 articles, 29 articles including 3158 samples were finally reviewed, of which 16 articles used PCR methods, 8 articles used serology method and 13 articles used other methods such as immunohistochemistry and in situ hybridization. The prevalence of the virus was higher in Asian and African countries such as Iraq and Egypt than other European and South American countries. Among these, the highest prevalence of the virus in different samples of patients with breast cancer was related to Iraq. Conclusion: The results of our study showed the higher prevalence of the virus in patients with breast cancer rather than normal subjects and reveal the role of the virus in the development of breast cancer.